The Relationship Between the Implementation of Statutory Preventative Measures, Perceived Susceptibility of COVID-19, and Personality Traits in the Initial Stage of Corona-Related Lockdown: A German and Austrian Population Online Survey - Eichenberg, Christiane; Grossfurthner, Martin; Andrich, Jeannine; Hübner, Lisa; Kietaibl, Sybille; Holocher-Benetka, Stefana (Frontiers in Psychiatry, 2021)
Background: Especially during the early and middle phases of the COVID-19 pandemic, the population's compliance in precautionary measures (e.g., hygiene rules, smart working, travel restrictions, and curfews) is paramount to prevent the virus from spreading. Objective: The investigation and documentation of different sociodemographic and personality-specific factors in the approach to preventive measures during the COVID-19 pandemic based on the Health Belief Model postulates on specific health behaviors. Method: An online survey conducted on N = 3003 individuals living in Germany and Austria in the early phase of the lockdown. The questionnaire comprised a self-administered section, exploring the dimensions posited in the Health Belief Model: perceived severity, perceived susceptibility, perceived barriers, perceived benefits of health-promoting measures, and health-related action. Additionally, the following standardized scales were used to record personality determinants: the Stress Coping Style Questionnaire SVF 78 to evaluate coping and processing strategies in stressful circumstances, the Positive and Negative Affect Schedule (PANAS) to assess the emotional state induced by the corona crisis, the UI-18 scale to diagnose the intolerance of uncertainty, and the State Trait Anxiety Inventory (STAI). Results: Following the Health Belief model, four groups were formed based on perceived susceptibility and engagement in health-promoting behaviors, and studied in relation to personality determinants. This typification has functional implications for inferring the appropriate support, notably to encourage compliance with the preventive regulations within the groups, which, for several reasons, showed poor abidance.